Entrevista a Miguel Giusti - Ibañez, Franklin (Con-Textos Kantianos. International Journal of Philosophy, 2024)
Miguel Giusti is a renowned specialist in German philosophy and a passionate promoter of academic events that lead to the analysis of the contemporary world. Recently, within the framework of the XXV World Congress of Philosophy in Rome, he was elected member of the Steering Committee of the International Federation of Philosophical Societies (FISP). In the interview, he tells us about his intellectual itinerary and gives an account of the persistent challenges to continue thinking about today.